Assessment of Meteorin-like Protein Serum Levels in Pre-diabetes and Newly Diagnosed Type 2 Diabetes Mellitus - Abdul Haleem, Saif Ali; Hamzah, Mohammed I.; Khudhair, Mahmood Shakir; Deli, Esraa Qais (AL-Kindy College Medical Journal, 2024)
Background: Meteorin-like, is an innovative adipokine, that exhibits elevated expression within adipose tissue and confers advantageous effects upon energy metabolism. Nevertheless, current research pertaining to circulating Meteorin-like levels in obesity remains limited and incongruent. Thus, the objective of this study was to assess Metrnl serum concentrations among adult individuals with pre-diabetes and newly diagnosed type 2 diabetes mellitus and examine its correlation with glucose, HbA1C, and lipid metabolism. Subjects and Methods: The case-control study incorporated 120 subjects, who were then segregated into three distinct groups, namely control (n = 60), pre-diabetes (n = 30), and newly diagnosed type 2 diabetes mellitus patient’s (n = 30). The quantification of serum Meteorin-like concentrations was undertaken by employing an enzyme-linked immunosorbent assay. Results: The data of the current study demonstrates a significant increase in the concentration of Meteorin-like protein in individuals with newly diagnosed type 2 diabetes mellitus patients as compared to those without the condition (p ≤ 0.001). A positive correlation between METRNL and various metabolic parameters, such as BMI, FBS, HbA1C, TC, TG, and LDL-C, was observed using the Pearson correlation coefficient. Conversely, a negative correlation was observed between METRNL and HDL-C as well as VLDL-C. Conclusions: The present study has revealed that serum Meteorin-like levels were found to be elevated in both individuals having newly diagnosed type 2 diabetes mellitus patients and pre-diabetes. Furthermore, the association between serum Meteorin-like levels and lipid profile was observed to be dependent. These findings strongly suggest that the modification of circulating Meteorin-like levels may serve as a promising biomarker for the prognosis of type 2 diabetes mellitus.